Peran Ketua Kelompok Tani Dalam Adopsi Teknologi Budidaya Bawang Merah Di Lahan Pasir Pantai Kecamatan Sanden Kabupaten Bantul - Eka Adi Satria P; Roso Witjaksono; Harsoyo Harsoyo (Agro Ekonomi, 2016)
The research was conducted in the District Sanden Bantul and has a goal to determine: (1) the degree of the role of chairman of farmer groups in technology adoption onion cultivation in the land of sand beach, (2) the factors which affect the role of chairman of farmer groups, and (3) the influence of the role of chair of farmer groups and other factors to adoption of red onion cultivation technology in coastal sandy farming land. The basic method used in this research is descriptive analytical with survey technique. The sample villages were selected purposively, that were Srigading Village and Gadingharjo Village. Data was analyzed by frequency distribution tables and multiple linear regression analysis. The results showed that the role of chairman of farmer groups in adoption of red onion cultivation technology in the hight category. The age, education, motivation, and field extension worker role of farmers influence significantly and positively to role of chairman of farmer groups in adoption of red onion cultivation technology. Factors that influence positively the adoption of red onion cultivation technology in the sandy land are the field extension worker role and the role of chairman of the farmer groups. The age, motivation, and education of farmer, has no effect onion cultivation technology adoption in the sandy beach land.